Management of Myasthenia Gravis - Venkataramaiah, Sudhir; Kamath, Sriganesh (Journal of Neuroanaesthesiology and Critical Care, 2019)
Myasthenia gravis (MG) apart from Guillain–Barré syndrome is one of the most common disorders presenting as respiratory failure secondary to muscle weakness in the modern world. MG is also one of the most researched and reasonably well understood autoimmune disorder of mankind. From the description of early cases of MG to the current day understanding, the progress in the management and therapeutics has advanced significantly. Diagnosis of MG can be accurately done either with traditional tests such as the edrophonium test or by advanced nerve conduction studies. Presence of demonstrable circulating autoantibodies against the acetyl choline receptors, muscle-specific tyrosine kinase, involvement of B and T cells in the pathogenesis, and tomographic evidence of the enlarged thymus gland in certain patients have led to designing specific treatment strategies. Removal of the circulating autoantibodies as much as possible by plasmapheresis supported by anticholinesterases and immunosuppression are the mainstay of targeted therapy. The advent of newer immunosuppressant drugs such as rituximab which targets the CD20 protein present on the surface of B cells and tacrolimus which is an interleukin 2 inhibitor has improved the therapeutic armamentarium of the physician. These agents in combination with time tested medications such as steroids and antimetabolites have rendered faster remission rates and improved outcomes in MG crisis. This article outlines the basic pathophysiology, specific and supportive management strategies in patients presenting with MG with or without crisis.
Keywords: acetyl choline receptor; anticholinesterase; immunoglobulin; myasthenia gravis; neuromuscular junction; plasmapheresis